2004
DOI: 10.1109/tns.2004.839141
|View full text |Cite
|
Sign up to set email alerts
|

High total dose tolerance of prototype silicon nanocrystal non-volatile memory cells

Abstract: Abstract-We report the first results pertinent to the high total dose tolerance of Si nanocrystal nonvolatile memory cells. The studied prototype nc-Si field effect transistors made by ion implantation retained virtually unchanged write/erase characteristics, typical for the two-state devices, to cumulative doses exceeding 15 Mrad(Si).Index Terms-Field effect transistors (FETs), nonvolatile memory (NVM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…All the programmed NC MOS capacitors undergo a bit flip 1→0 following irradiation, (Fig. 21b), in agreement with Petkov (Petkov et al, 2004) . If the oxide trapped charge is not removed from the oxide a permanent shift of the memory window would result, causing serious problems in reading the memory state.…”
Section: Effects On F-n Injectionsupporting
confidence: 84%
See 2 more Smart Citations
“…All the programmed NC MOS capacitors undergo a bit flip 1→0 following irradiation, (Fig. 21b), in agreement with Petkov (Petkov et al, 2004) . If the oxide trapped charge is not removed from the oxide a permanent shift of the memory window would result, causing serious problems in reading the memory state.…”
Section: Effects On F-n Injectionsupporting
confidence: 84%
“…The initial, dose dependent, radiation induced shift disappears gradually by increasing the voltage sweep. Therefore, the memory window of irradiated devices approaches the memory window of the unirradiated devices, as also reported by Petkov (Petkov et al, 2004). In particular it was found that the radiation induced oxide charge can be removed with 1 write or erase pulse as shown in Fig.…”
Section: Effects On F-n Injectionsupporting
confidence: 78%
See 1 more Smart Citation
“…Several techniques of nanocrystal formation have recently been developed based on chemical vapor deposition (CVD) of Si nanocrystals onto an oxidized Si substrate, ion implantation of Si or Ge into SiO 2 , annealing of a silicon-rich oxide, aerosol deposition, etc. [4].…”
Section: Introductionmentioning
confidence: 99%
“…While some works already investigated the effect of ionizing radiation on FG Flash memories [14]- [17], until now, few works have investigated this issue in NCMs [18], [19]. Oldham, et al, [18] reported better resistance of NCMs under heavy-ion irradiation compared to Flash memories, without any degradation of the NCM cell retention characteristic.…”
Section: Introductionmentioning
confidence: 99%